2012
DOI: 10.1080/17429145.2011.597002
|View full text |Cite
|
Sign up to set email alerts
|

Response of barley to root colonization byPseudomonassp. DSMZ 13134 under laboratory, greenhouse, and field conditions

Abstract: Beneficial rhizobacteria strains are of substantial interest as biological plant protection agents in agriculture. Bacteria of the genus Pseudomonas have been studied for many years for their role in plant growth and biocontrol. In this study, we analyzed the influence of the commercially available agent Proradix † , which contains the strain Pseudomonas sp. DSMZ 13134, on barley. In controlled infection experiments, we showed that Pseudomonas sp. DSMZ 13134 induces resistance to the barley leaf pathogen Rhync… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 41 publications
0
28
1
Order By: Relevance
“…Authors observed significant increase in the shoot length, root length, and fresh and dry seedling weight. Fröhlich et al (2012) found that inoculation with PGPR, i.e. Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 99%
“…Authors observed significant increase in the shoot length, root length, and fresh and dry seedling weight. Fröhlich et al (2012) found that inoculation with PGPR, i.e. Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 99%
“…A number of different approaches have been investigated with the intention to reduce fertilizer inputs into agroecosystems, including breeding plant varieties with better P acquisition efficiency [6], fertilizer placement strategies [7], or application of soil organisms and natural extracts with plant growth-promoting potential [8][9][10]. These so-called bio-effectors (BEs) include plant growth-promoting rhizobacteria (PGPR) for instance Pseudomonas and Bacillus spp., as well plant-associated fungi, such as arbuscular mycorrhizal fungi (AMF) or Trichoderma spp.…”
Section: Introductionmentioning
confidence: 99%
“…Some BEs induce plant growth by stimulating the plant's own hormone production such as auxins or cytokinins [13,14], or by producing directly hormone-like compounds [15]. Regarding P acquisition, some BEs are associated with increased phosphatase activities in the soil [16][17][18] and have also shown the ability to liberate P from soil particles [9,16,19,20] and from P-recycling fertilizers [21,22]. Another important mechanism is based on the so-called "mycorrhiza helper" effect [23] which has been observed for many bacterial BEs [24].…”
Section: Introductionmentioning
confidence: 99%
“…have been broadly studied for their roles in plant growth promotion and biological control [16,17,21,25,30,46,59]. Plant growth promoting activities of Pseudomonas spp.…”
Section: Introductionmentioning
confidence: 99%
“…Plant growth promoting activities of Pseudomonas spp. include production of indole acetic acid (IAA) [16], phosphate solubilization [60], degradation of toxic compounds [38] and production of biocontrol agents against fungal phytopathogens like the production of siderophores [7,14] or antibiotics [21,24] as well as against insect pests by the production of insect toxins [41].…”
Section: Introductionmentioning
confidence: 99%